Corporate branding effects on consumer purchase preferences in Serbian telecom market - Vanka, Gajo (Applied Studies in Agribusiness and Commerce, 2010)
This research is carried out to know the role of corporate branding in mobile phone network along with different influencing factors involved in the purchase of mobile telephone connections. This paper discusses corporate branding from consumer’s point of view that how much they value it and what type of role it has.This is a quantitative study. A questionnaire is used in order to investigate corporate branding and other influencing factors involved in purchase decision of the customers. Population selected for this study are Belgrade University students which is the most of Serbian youth segment and is a valuable source that gives precise information with high probability about market preferences according to the Research of Serbian republic statistical office. Primary data are obtained by collecting data from questionnaire and interview, while the secondary data are collected from various reliable sources. Primary data provide reliable content in accordance with a secondary data obtained by Serbian republic statistical office and with a Research of competitor and consumer preferences insight provided by Telenor Company. The analysis of the data has been performed in accordance with the chosen theories and summarized in a table, which serves as a tool for deriving reliable and relevant conclusions. The sample size was determined by conducting a primary study and defining the variance of primary sample and the intended number of samples was selected carefully and randomly from the population. Then the validity and reliability of the questionnaire was determined. The used questionnaire in this research consisted of 7 common, and 30 specialized questions which were supporting the hypotheses of the research. Data was analyzed using the frequency percent techniques, and in the chapter related to the deductive statistics, one-sample t test was used to analyze and approve/disapprove the questions supporting the research hypotheses. The analysis of this study reveals different set of results while making comparison between literature and empirical. It investigates the relative importance of the corporate branding to the customers in mobile phone telecommunication industry while making purchase decision. The findings of this study provided useful information which is helpful not only for the students but also for the brand managers of mobile telecom operators that how they can improve their company’s strategic position for longer period of time through corporate branding to trigger more customers and for a good brand.